Chemically deposited blocking layers on FTO substrates: Effect of precursor concentration on photovoltaic performance of dye-sensitized solar cells - Yoo, Beomjin; Kim, Kang-Jin; Bang, So-Yeon; Ko, Min Jae; Kim, Kyungkon; Park, Nam-Gyu (ELSEVIER SCIENCE SA, 2010)
Blocking layers are formed on the conductive fluorine-doped tin oxide (FTO) substrate by using titanium (IV) bis(ethylacetoacetato) diisopropoxide precursor solutions with different concentration to investigate the effect of the precursor concentration on thickness and morphology of blocking layers and photovoltaic property in dye-sensitized solar cell. Increase in the precursor concentration from 0.05 M to 1.2 M leads to increase in the blocking layer thickness from 10 nm to 240 nm. Besides increase in the thickness, nanoparticulate intralayer morphology is developed as increasing the precursor concentration. Photovoltaic property, especially photocurrent density (J(SC)), is influenced by the precursor concentration, where J(SC) increases with increasing the concentration, reaches maximum at around 0.1 M (blocking layer thickness is about 20 nm), decreases gradually up to 0.4 M and become close to the value without blocking layer for further increase in the concentration. Photovoltages increase slightly after formation of blocking layer, but not significantly altered compared with the extent of photocurrent change. It has been found that the precursor concentration with around 0.1 M provides the optimum condition to protect the loss of electrons within our experimental condition and at this condition the photoconversion efficiency is able to be enhanced by about 6% compared with that without blocking layer. Electrochemical impedance spectroscopic study shows that the dependence of photovoltaic property on Ti precursor concentration is closely related to the charge transfer resistance at the blocking layer/electrolyte interface, where the electron loss at near FTO substrate is effectively protected by the blocking layer with the maximum charge transfer resistance. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: CONDUCTING GLASS/TIO2 INTERFACES; IMPEDANCE SPECTROSCOPY; CONVERSION EFFICIENCY; BACK-REACTION; TIO2; RECOMBINATION; TRANSPORT; ELECTRODES; FILM